The effect of nursing consultation based on orem's theory of self-care and Bandura's concept on infertility stress - Asmaa Zaidouni; Fatima Ouasmani; Amal Benbella; Jalal Kasouati; Rachid Bezad (Wolters Kluwer Medknow Publications, 2019)
Introduction: Infertility is one of the most stressful experiences in a couple's life. Several approaches have been proposed to manage infertility stress during the medically assisted technology process. Objective: The objective was to examine the effect of nursing consultation on the stress experienced by infertile couples before starting infertility treatment. Materials and Methods: This cross-sectional study was conducted from November 2017 to November 2018 among 120 infertile couples (240 patients) for whom stress was assessed. One hundred and thirteen patients of them who had a high infertility stress level were invited to participate in this randomized study (57 were assigned to the control group and 56 were included in the intervention group). The intervention group received nursing consultation based on Orem's theory and Bandura's concept in addition to the routine nursing care. Perceived Stress Scale-10 (PSS-10) and General Self-Efficacy Scale (GSES) were used before and after nursing intervention. Statistical Analysis: The Chi-square test followed by a paired t-test and independent t-test was used for data analysis by SPSS software (version 20). Results and Discussion: There were no statistically significant differences before nursing intervention between the two groups in terms of PSS-10 (t = 1.18, P = 0.23) and GSES (t = −0.40, P = 0.689) scores, but a significant difference emerged in the intervention group following the nursing intervention: a reduction of the PSS score (t = −8.91, P = 0.000) and an increase in the GSES score (t = −5.25, P = 0.000, with 95% confidence interval (CI)). Conclusion: Nursing consultation has been shown to be beneficial in decreasing perceived stress and increased self-efficacy for infertile couples undergoing assisted reproductive technologies.